Electronic structural investigation of Ni-doped CeO2-Y for catalytic hydrogen production: exsitu XRD, XAS, and XPS study - Thakur, Vishal; Gautam, Sanjeev; Rajput, Parasmani; Jee, Hae-Geun; Chakraverty, Suvankar; Gupta, Mukul; Chae, Keun Hwa; Hwang, Chan-Cuk (Elsevier, 2025)
Cerium oxide (CeO2-Y) possesses exceptional redox properties, making it valuable for hydrogen production and greenhouse gas conversion. Nickel (Ni) doping enhances its reactivity, and this study investigates the effect of Ni doping (0-7%) on the structural, electronic, and optical properties of CeO2-Y. The Ce1-xNixO2-Y (0 <= x <= 0.07) system was synthesized via the sol-gel method and analyzed using XRD, XAS, XPS, UV-DRS, and PL spectroscopy. XRD Rietveld refinement and EXAFS studies revealed a decrease in lattice parameters and increased oxygen vacancies around Ce at low Ni doping (<= 1%), while higher doping increased lattice parameters and eliminated vacancies. XANES analysis indicated a shift towards a higher Ni oxidation state with increasing Ni content, and substitutional(cubic) and interstitial(octahedral) nature of Ni-doping when simulated by FEFF ver 9.05 code. XPS and PL analyses suggested Ni's electron donor behavior, along with an increase of Ce3+ oxidation state concentration from almost 10% in pristine CeO2-Y to almost 23%-25% with Ni-doping. The results suggest Ce substitution by Ni-ions at low doping, with interstitial occupation at higher Ni-doping concentrations. Surface-sensitive XPS and bulk XAS indicated variations in Ce3+ concentrations. UV-DRS confirmed the two Ni-dopant types with change in bandgap as a function of Ni-doping concentration. These findings provide crucial insights into transition metal doping in CeO2-Y catalysts, enhancing their efficiency for sustainable applications.